A Modification of Conjugate Gradient Method using Strong Wolfe Line Search - V. Mandara, Abba; Mamat, Mustafa; Y. Waziri, M.; fendee Mohamed, Mohamad A (International Journal of Engineering and Technology, 2018)
In this paper, a proposed modification of conjugate gradient (CG) coefficient  method to solve unconstrained optimization problems is presented. A strong - Wolfe line search is used to generate  with sufficient descent direction and global convergence property is established. Numerical result are also presented based on the number of iterations and CPU times, the results have shown that the modified  performs better compare to other CG methods.